Assessment of the Effect of Oral Health Education with Use of Plaque-Disclosing Agent on Knowledge and Plaque score of Primary School Children - Bhattarai, Rosina; Thapa, Vinita; Basnyat, Srijan Singh (Journal of Nepalese Association of Pediatric Dentistry, 2024)
Introduction: Poor oral hygiene and dental diseases are significant public health concerns among children however many children lack adequate knowledge about proper oral hygiene and often fail to visualize or remove plaque effectively. Efforts to remove this gap between knowledge and practice can be made in school where children spend a substantial time and are receptive to learning. Objective: This study aimed to evaluate the impact of oral health education on the knowledge and plaque score of primary school children. Methods: Quasi-experimental study with pre-and post-design without control group was conducted among 423 primary-level school children from four schools in Bharatpur. Closed-ended questionnaire was prepared by the researcher with ten questions in total, which was translated into local language for primary-level school children. Descriptive and inferential statistical methods, including the Paired t-test, were carried out. Results: Oral health knowledge was assessed at baseline and one-week follow-up. Results demonstrated improvements in identification of permanent teeth count (82.3% to 91.3%), understanding of beneficial foods and drinks (96.7% to 97.6% and 94.8% to 96.5% respectively) and awareness of anticariogenic components in toothpaste (46.5% to 66.7%). Decrease observed in knowledge related to the importance of teeth in speech. Paired t-test was applied and there was statistically significant difference in plaque index scores before and after health education with decrease from 0.84 to 0.72. Conclusion: In general, oral health education has positive effect on improving the knowledge of the school children. Reinforcement in health education should be done to have the lasting effect in children.